2013
DOI: 10.1038/ja.2012.118
|View full text |Cite
|
Sign up to set email alerts
|

PJS, a novel isocoumarin with hexahydropyrimidine ring from Bacillus subtilis PJS

Abstract: Amicoumacin group of antibiotics, such as baciphelacin, 1 amicoumacins, 2 AI-77s, 3 xenocoumacins, 4 Y-05460M-A, 5 PM-94128, 6 Sg17-1-4, 7 bacilosarcins A, B 8 and lipoamicoumacins A-D, 9 is a small family of isocoumarin, which possesses the common chromophore, 3, 4-dihydro-8-hydroxyisocoumarin. Most members of amicoumacin group of antibiotics are produced by the genus Bacillus and exhibit various important bioactivities. The chromophore shows specific UV absorbance at 247 and 314 nm in methanol. Thus, a proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…The structure-activity relationships of these dichloroisocoumarins indicated that a hydroxyl group was more significance than a methoxy group on anti-inflammatory activity. Isocoumarins were previously reported to have radical scavenging and antioxidant [ 14 ], anti-HIV [ 15 ], antimicrobial [ 16 ], anti- γ -secretase [ 17 ], antitumor [ 18 ], immunomodulatory [ 19 ], antifungal [ 20 ], toxicity to zebrafish embryos [ 13 ], and α -glucosidase inhibitory activities [ 21 ]. This is the first report of anti-inflammatory activity of dichloroisocoumarins.…”
Section: Resultsmentioning
confidence: 99%
“…The structure-activity relationships of these dichloroisocoumarins indicated that a hydroxyl group was more significance than a methoxy group on anti-inflammatory activity. Isocoumarins were previously reported to have radical scavenging and antioxidant [ 14 ], anti-HIV [ 15 ], antimicrobial [ 16 ], anti- γ -secretase [ 17 ], antitumor [ 18 ], immunomodulatory [ 19 ], antifungal [ 20 ], toxicity to zebrafish embryos [ 13 ], and α -glucosidase inhibitory activities [ 21 ]. This is the first report of anti-inflammatory activity of dichloroisocoumarins.…”
Section: Resultsmentioning
confidence: 99%
“…The preparation of the agar slant and cultural broth of strain PJS were the same as described previously [ 14 ]. The strain was inoculated into three 500 mL Erlenmeyer flasks containing 100 mL of modified Gause’s No.1 cultural broth (soluble starch 20.0 g, NaCl 50.0 g, K 2 HPO 4 0.5 g, KNO 3 1.0 g, MgSO 4 1.0 g, FeSO 4 0.02 g, glucose 1.0 g, peptone 0.5 g, tryptone 0.3 g, and N -acyl-asparagine 0.5 g in 1.0 L distilled water, pH 8.0), and cultured on a rotary shaker at 180 rpm and 28 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The structural variations are ascribed to the differences in an aliphatic, carbohydrate-like chain connected with the dihydroisocoumarin nucleus by an amido bond. To date, more than 40 amicoumacin analogs have been reported and they exhibit a wide range of biological activities, such as antibacterial [ 12 , 13 , 14 , 15 ], antifungal [ 16 ], anticancer [ 17 , 18 , 19 ], anti-inflammatory [ 20 ], antiulcer and herbicidal effects [ 21 , 22 ]. Many amicoumacins showed excellent inhibitory activities against Gram-positive bacteria, especially the methicillin- or oxacillin-resistant strains of Staphylococcus aureus (MRSA or ORSA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our ongoing research on novel amicoumacin products from Bacillus spp. [13,14], the strain Bacillus subtilis XZ-7, isolated from a soil sample collected from Damxung county in Tibet, China, was chosen through the chemical screening approaches and dereplication strategies [15]. Previous investigations of the strain XZ-7 have resulted in the identification and isolation of a series of amicoumacin compounds [15,16].…”
Section: Introductionmentioning
confidence: 99%